Criminal Acts of Persecution That Resulted in The Death of The Victim - Ruth Febriani Hia; Ojak Nainggolan (Journal Equity of Law and Governance, 2025)
This study discusses the criminal act of assault that resulted in death, focusing on the case study of Decision Number 467/Pid.B/2022/PN Stb. The purpose of this research is to explore the importance of applying the principle of "equality before the law" in upholding justice and to assess whether the punishment imposed is appropriate given the consequences of the defendant's actions. This research uses a normative legal method with a statute-based approach, examining relevant regulations and laws related to cases of assault resulting in death. In this case, assault is defined as an act that causes pain or injury to the body, leading to the victim's death. The defendant was sentenced to 1 year and 7 months in prison under Article 351 paragraph (3) jo. Article 55 paragraph (1) point 1 of the Criminal Code. However, the analysis shows that the sentence is considered too lenient given the impact of the defendant's actions. Therefore, this study recommends that stricter law enforcement be applied to provide a deterrent effect and better justice for society.